Role of vegetation in slope stability: case studies of forested slopes in the Mahabharat Range, Nepal - Timilsina, Yajna Prasad; Sharma, Ram Prasad; Paudel, Prakash (Journal of Nepal Geological Society, 2012)
Available with full text.